1987
DOI: 10.1002/pola.1987.080250908
|View full text |Cite
|
Sign up to set email alerts
|

FT–IR spectroscopic study on the thermal and thermal oxidative degradation of nylons

Abstract: SynopsisThe effects of heat and oxygen on nylon films were studied by FT-IR spectroscopy. Nylons 6, 66 and nylons containing carbonyl groups in either the diamine or the diacid moiety were prepared. Nylon f i l m s cast on aluminum were studied in an environmental chamber under controlled conditions. The progress of chemical and physical changes was monitored by FT-IR spectroscopy. Thermal energy caused largely an increase in crystallinity due to annealing and also an increase of nonhydrogen-bonded amide group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…2 (i)) [25]. Bands at 1640 cm -1 and 1547 cm -1 could be attributed to C=O stretching vibrations (Amide I band) and N-H bending vibrations (Amide II band) [26,27], respectively. The spectra of the coated fabric before and after stretching were characterized by typical features of PPy [28,29].…”
Section: Infrared Spectroscopymentioning
confidence: 92%
“…2 (i)) [25]. Bands at 1640 cm -1 and 1547 cm -1 could be attributed to C=O stretching vibrations (Amide I band) and N-H bending vibrations (Amide II band) [26,27], respectively. The spectra of the coated fabric before and after stretching were characterized by typical features of PPy [28,29].…”
Section: Infrared Spectroscopymentioning
confidence: 92%
“…It has been reported that the low frequency peak at 1639 cm Ϫ1 within the CAO stretching band is associated with the hydrogenbonded CAO bonds, and the peak at 1643 cm Ϫ1 is assigned to "free" carbonyl bonds. 28,29 The appearance of shoulders between 1650 and 1700 cm Ϫ1 were also interpreted as the formation of different types of carbonyl compounds during the thermal degradation/oxidation of nylon. 29 Accordingly, the observed decrease in the height of the peak at 1639 cm Ϫ1 in the metallized acid dye containing nylon samples indicates the decrease in hydrogen bonding between the amide groups of the nylon chains.…”
Section: Interaction Between Nylon and Dyestuffsmentioning
confidence: 99%
“…Polyamides containing primary amino end-groups show yellowing almost from the start of oxidation, whereas their molecular weights drop much more slowly [123][124][125][126][127][128][129][130][131][132][133]. Amine end groups can initiate the homolysis of hydroperoxides too, but primarily they condense with aldehydes generated by oxidation to aldimines [134].…”
Section: Polyamides Pa46 Pa6 Pa66 Semi-aromatic Polyamides -Degradmentioning
confidence: 99%